Pengaruh Motivasi, Modal Ivestasi Minimal Dan Persepsi Resiko Terhadap Minat Mahasiswa Universitas Negeri Di Bali Untuk Berinvestasi Pada Masa Pandemic-Covid-19 (Studi Kasus Mahasiswa S1 Akuntansi Universitas Pendidikan Ganesha dan Universitas Udayana) - Sinta Suci Prasini; Nyoman Trisna Herawati (Universitas Pendidikan Ganesha, 2022)
This study aims to determine the effect of motivation, minimal investment capital and risk perception on the interest of public university students in Bali to invest during the covid-19 pandemic. This study uses a quantitative approach. Data were collected by using a questionnaire as a research instrument. This data is primary data because the data is obtained directly from the respondents' answers in the questionnaire distributed via google form. All students of S1 Accounting Study Program, Faculty of Economics, Ganesha University of Education and Udayana University were used as the population in this study. From the entire population, the sample was determined by purposive sampling method. Based on the sampling method, the samples obtained were 285 respondents. The data analysis technique used is descriptive statistical test, classical assumption test and multiple linear regression analysis using SPSS 20.0 for Windows program. The results showed that motivation (X1) and minimal investment capital (X2) had a significant positive effect, for risk perception (X3) had a significant negative effect on interest in investing.